Politik Hukum Putusan MK Nomor 36/PUU-X/2012 dalam Upaya Mengembalikan Kedaulatan Negara dan Perlindungan HAM - Asnawi, Habib Shulton (Mahkamah Konstitusi Republik Indonesia, 2016)
The background of this paper departs from concern over the fragility of the value of Indonesia's sovereignty which has an impact on the violations of the rights of Indonesian citizens (human rights). Law No. 22 of 2001 on Oil and Gas (Oil and Gas Law) has undermined the sovereignty of the state and the nation's economic sovereignty. Oil and Gas Law poses systemic impact on people's lives and could harm the country's finances. This is because oil and gas law opened liberalization of oil and gas management which is highly dominated by foreign entity since oil and gas world in Indonesia is dominated by foreign companies up to 89 percent. Therefore, in an effort to restore the sovereignty of the Republic of Indonesia in the field of oil and gas, the Constitutional Court as a State institution has taken progressive step in its decision No. 36 / PUU-X / 2012 on the dissolution of BP Migas. The legal policy of the Court decision constitute a wise choice and is a progressive step in the field of law, especially the protection of human rights of the people of Indonesia.